The fox and the hound: in-depth and in-grain Na doping and Ga grading in Cu(In, Ga)Se2 solar cells. Issue 14 (30th March 2020) - Colombara, Diego; Conley, Kevin; Malitckaya, Maria; Komsa, Hannu-Pekka; Puska, Martti J.
Abstract : Highly efficient chalcopyrite photovoltaic cells display complex distributions of sodium dopant and gallium: how are these distributions related to each other? Abstract : Cu(In, Ga)(S, Se)2 (CIGS) thin film solar cells require appropriate depth and lateral distributions of alkali metal dopants and gallium to attain world record photovoltaic energy conversion. The two requirements are interdependent because sodium is known to hamper In/Ga interdiffusion in polycrystalline films. However, such a fact is challenged by recent findings where sodium appears to enhance In/Ga interdiffusion in monocrystalline films. This contribution reviews closely the two cases to the benefits of grain boundary engineering in CIGS. A computational model reveals why Na induces In accumulation at CIGS grain boundaries, confining Ga to grain interiors. The positive technological implications for wider gap chalcopyrites are stressed.